Pengaruh Literasi Keuangan, Modal Usaha, dan Pengembangan Pariwisata Terhadap Pendapatan Pelaku Usaha (Survey pada UMKM Pesona Wisata Pasar Dhoplang di Kecamatan Slogohimo Kabupaten Wonogiri) - Anjani Mawar Sari; Setyaningsih Sri Utami (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of financial literacy, business capital, and tourism development on the income of MSME entrepreneurs in the Pesona Wisata Pasar Ndhoplang area, Slogohimo District, Wonogiri Regency. MSMEs play an essential role in developing the local economy, especially in tourism areas. However, many MSME actors face challenges in financial management, limited capital, and suboptimal tourism development that affect their business income. Prior to regression analysis, this study conducted classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation tests to ensure model validity. Further analysis involved partial tests (t-test), simultaneous tests (F-test), and the calculation of the coefficient of determination (R²) to measure the model’s explanatory power. The results indicate that financial literacy, business capital, and tourism development have a positive and significant effect on MSME performance. The F-test confirmed that all three independent variables simultaneously have a significant influence on the dependent variable. The coefficient of determination (R²) demonstrates that variations in MSME performance can be substantially explained by financial literacy, business capital, and tourism development, while the remaining variation is influenced by other factors outside the research model.